Avaliação da degradabilidade ruminal in situ das silagens de milho (Zea Mays, L.) com diferentes graus de vitreosidade e com perfil de aminoácidos modificados - Fernando Pimont Pôssas (2007)
The aim of this work was to evaluate the ruminal in situ degradability of corn silage with differents vitreousness and modified aminoacids profile. The experiment was carried out at Embrapa Milho e Sorgo (Sete Lagoas, MG,Brazil) and the chemical analyses at Escola de Veterinária da Universidade Federal de Minas Gerais (Belo Horizonte,MG, Brazil) and at Embrapa gado de Leite (Juiz de Fora, MG, Brazil). The experiment evaluated the ruminal in situ degradability of dry matter (DM), crude protein (CP), starch, neutral detergent fiber (NDF), acid detergent fiber (ADF) e hemicellulose of four genotypes of corn silages: QPM-129 (flint corn with modified aminoacids profile), BRS-3060 (semi-flint), AG-1051 (dent corn) and SHS-4040 (flint corn, showing higher vitreousness), harvested 120 days after sowing. The experimental design was the 4x4 Latin Square. As for ruminal incubation was utilized nailon bags, that were withdrawed after six, 24 and 96 hours of ruminal incubation. The levels of DM, CP, satrch, NDF, ADF, hemicellulose, celulose and lignin analyzed in silages were: 47,3, 48,1, 47,6 and 46,1%; 8,20, 8,51, 7,10 and 7,66%; 35,49, 44,30, 38,14 and 35,69%; 52,41, 44,12, 44,57 and 56,55%; 26,23, 22,63, 23,33 and 25,36%; 26,17, 21,49, 21,24 and 31,18%; 19,53, 16,74, 18,34 and 17,11% and 4,09, 3,32, 3,75 and 3,87% to QPM 129, AG 1051, BRS 3060 and SHS 4040 hybrids silages, respectively. Within the six hours of incubation time, there were no statistical differences (p<0,05) in the ruminal desappearance of DM, while only AG 1051 hybrid e SHS 4040 showed the highes ruminal desappearance. Within the 24 and 96 hours of incubation time, there were no statistical differences (p<0,05) among treataments. The AG 1051 genotype showed the highest degradation potencial maximum (A) of DM (77,88%), the highest soluvel fraction (S) (36,52%), the highest effective degradability (ED), the lowest degradation constant rate (c) (3,1%/h) and the SHS 4040 genotype showed the highest “c” (4,7%/h). The genotype AG 1051 didn’t showed statistical difference (p<0,05) among the incubation time of six and 24 hours and showed the highest ruminal desappearance of CP (p<0,05) to the incubation time of six hours. The AG 1051 genotype showed the highest value of “S” and the highest ED of CP. The SHS 4040 genotype showed the lowest ED of CP. The AG 1051 didn’t showed statistical difference (p<0,05) in the starch ruminal desappearence among the incubation time. The others genotypes showed statistical difference (p<0,05) in the starch desappearance ruminal among the time of six hours and the times of 24 and 96 hours. The AG 0151 and SHS 4040 genotypes showed the highest starch desappearance ruminal (p<0,05) to the incubation time of six hours. The AG 1051 showed the highest starch soluvel fraction “S”, the highest “A”, the highest “c” and highest ED of starch. The SHS 4040 showed the lowest starch “S” and the lowest EF of starch. The SHS 4040 showed the highest NDF ruminal desappearance (p<0,05) in the incubation time of six hours. As for all genotypes there were meaningful increase (p<0,05) in the NDF ruminal desappearance with the incrase of time of six to 96 hours of ruminal incubation. The AG 1051 genotype showed the highest “A” (72,95%) and the lowest degradation constant rate “c” (1,3%/h). The SHS 4040 showed the highest NDF ED. There were no statistical difference (p<0,05) among the genotypes in incubations time analyzed to the ADF ruminal desappearance. There were statistical difference (p<0,05) among the incubations time analyzed to all genotypes. The SHS 4040 genotype showed the highest “A” (73,0%), the highest “S” (7,96%), the highest potential degradable fraction (b) and highest ADF ED. The BRS 3060 genotype showed the lowest ADF value of “b” and of “A”. The SHS 4040 genotype showed the highest value of hemicellulose ruminal desappearance (p<0,05) for the incubation time of six hours. The SHS 4040 showed the highest hemicellulose value of “c” (2,6%/h), the highest “S” and highest EF. The AG 1051 showed the lowest hemicellulose value of “c”, the highest “A” and highest “b”. All silages evalueted showed good ruminal degradability, being suggested its utilization as silage.